1964
DOI: 10.1177/004051756403400103
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Factors Influencing the Tensile Fatigue Behavior of Yarns

Abstract: A new instrument capable of recording the load-extension behavior of a yarn in cyclic testing is described. The instrument is constructed in such a fashion that it is possible to vary both the humidity and the temperature of the air in which the yarn is tested. Frequency and amplitude are also variable over a limited range.It is shown that the range of fatigue lifetimes of yarns in cycling conforms to the Weibull distribution, which is based on the theory of extreme values. Experimental evidence indicates that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1967
1967
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Substituting equation (1) in (3) will give: (4) Performing the differentiation on the left and writing the definition of the hyperbolic sine function in terms of exponential functions on the right would yield: (5) Equation (5) is a nonlinear differential equation and can not be solved analytically. Taylor expansion for an exponential function is as follows: (6) In order to linearize equation (5), we substitute the first order of Taylor expansion for the exponential function on the right side to get: (9) Equation (9) is a first order linear differential equation with the following integration factor: (10) The general solution of equation (9) is: (11) In equation (11), C is the integration constant and is determined using boundary condition.…”
Section: Theoretical Analysesmentioning
confidence: 99%
“…Substituting equation (1) in (3) will give: (4) Performing the differentiation on the left and writing the definition of the hyperbolic sine function in terms of exponential functions on the right would yield: (5) Equation (5) is a nonlinear differential equation and can not be solved analytically. Taylor expansion for an exponential function is as follows: (6) In order to linearize equation (5), we substitute the first order of Taylor expansion for the exponential function on the right side to get: (9) Equation (9) is a first order linear differential equation with the following integration factor: (10) The general solution of equation (9) is: (11) In equation (11), C is the integration constant and is determined using boundary condition.…”
Section: Theoretical Analysesmentioning
confidence: 99%
“…The controversy of unimodal and bimodal distributions for tensile fatigue behavior of yarns has been extensively reported and discussed by various researchers [ 3-5, 8, 23, 24, 29, 30 ] . Earlier studies of the tensile fatigue of yarns reported bimodal distributions of fatigue lifetimes [ 3 ], but later studies revealed a preponderance of unimodal Weibull distribution [4,14,23 ] . This poses a formidable problem in understanding the mechanism of yarn failure under cyclic tensile loading, since the mechanism involved in bimodal behavior is inherently different from that in unimodal Weibull distribution.…”
Section: Introductionmentioning
confidence: 97%
“…The ultimate behavior of such staple and multifilament yarns relates to the fatigue behavior of individual fibers and filaments. As with other engineering materials, research workers have studied the fatigue behavior of fibers [ 19,22,[26][27][28] , yams [2,7,9,14,23 ] , tire cords [10,16,34 ] , and fabrics [ 11 ] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He stated that the stretching and relaxation of yarn filaments and yarns during fabric deformation resulted in spasmodic pumping of the liquid and led to its distribution over a wide region of the fabric, thus improving the rate of evaporation. Frank and Singleton (1964) designed an instrument capable of recording the load-extension and load-relaxation behaviour of a yarn in cyclic testing, from which energy loss factors of yarn were studied. Otaghsara, Jeddi, and Mohandesi (2009) investigated the tensile and fatigue behaviour of different structures of warp knitted fabrics of different course density.…”
Section: Introductionmentioning
confidence: 99%